Part-time vocational education and training - rarely chosen, yet good examination pass rates - Uhly, Alexandra [Verfasser] (My University, 2020)
"Part-time vocational education and training in the dual system was regulated by law in 2005. Annual reporting has shown that very few part-time training contracts have thus far been concluded within the dual system. But how does vocational education and training unfold if trainees pursue it on a part-time basis? This article uses the Vocational Education and Training Statistics to analyse the success of part-time training contracts in 2018." (author's abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; Berufsausbildung; Teilzeitberufsausbildung; Ausbildungserfolg; Ausbildungsabbruch